A Pseudo-Stokes Mesh Motion Algorithm (Advances in Applied Mathematics and Mechanics, 2013)
This work presents a moving mesh methodology based on the solutionof a pseudo flow problem. The mesh motion is modeled as a pseudo Stokesproblem solved by an explicit finite element projection method. The meshquality requirements are satisfied by employing a null divergent velocitycondition. This methodology is applied to triangular unstructured meshesand compared to well known approaches such as the ones based on diffusionand pseudo structural problems. One of the test cases is an airfoil witha fully meshed domain. A specific rotation velocity is imposed as theairfoil boundary condition. The other test is a set of two cylindersthat move toward each other. A mesh quality criterion is employed toidentify critically distorted elements and to evaluate the performanceof each mesh motion approach. The results obtained for each test caseshow that the pseudo-flow methodology produces satisfactory meshesduring the moving process.